Sabedoria popular no uso de plantas medicinais pelos moradores do bairro do sossego no distrito de Marudá - PA - FLOR, Alessandra Simone Santos de Oliveira (Universidade Federal do Pará, 2017)
In the Amazon medicinal plants are a relevant resource for the treatment of several diseases, given the cultural context, access, reliability and low cost compared to industrial medicine. Inside this context, it is located the Marudá District, in the municipality of Marapanim,160 km far from Belém state of Pará, where it is common to use medicinal plants in order to treat health problems. In this sense, this work investigates the popular phytotherapy practice of herbal medicine practiced by the residents of the“Sossego” neighborhood in the District of Marudá-PA, illustrating the importance of medicinal plants for this human group in cultural, economic and environment context. For such purpose, we used a ethnopharmaceutical survey aiming to offer a prospecting tool of these plants employed as a therapeutic resource for the local population.